Automating the process of calculating the singular points and modeling the phase diagrams of multicomponent oxide systems - Krivileva, S. P.; Zakovorotniy, A.; Moiseev, V.; Ponomareva, N.; Zinchenko, O. (Institute for Single Crystals, 2019)
To automate the processes of calculating elements of state diagrams of multicomponent eutectic type oxide systems and simulate them, a calculation algorithm and an application package using function libraries has been developed. On the example of binary and ternary systems FeO-Cr2O3-SiO2, BeO-MgO-TiO2, BeO-MgO-ZrO2, Ca3(PO4)2-CaF2, their functionality was tested. The experimental verification of the compositions of singular points (binary and triple eutectics and van Rijn points) and melting temperatures in them by high temperature microscope in situ has shown good correlation between the experimental and calculated data.
Keywords: automation of calculations; multicomponent systems; van Rijn melting point; eutectic; modeling of state diagrams